Understanding bullying in Nigerian schools: Insights on prevalence, impacts, and solutions - Okoro, Chinedu I; Guliyeva, Nazrin; Eze, Kelechi Chidiebere; Mbang, Clarisse (PT. Pena Produktif Kreatif, 2025)
Bullying represents a significant issue in Nigerian schools, with a detrimental impact on students' psychological, social, and academic well-being. This systematic literature review aims to comprehensively understand bullying in the Nigerian context, examining its prevalence, contributing factors, impacts, and intervention strategies. The review included studies published in the last ten years and sourced from Google Scholar. The findings indicate that bullying in Nigeria manifests in diverse forms, including physical, verbal, relational, and cyberbullying. These forms exhibit variations based on age, gender, and regional factors. The contributing factors are numerous and complex, encompassing individual characteristics, family dynamics, school environments, and socio-cultural influences. The consequences of bullying for victims are significant, resulting in anxiety, depression, social isolation, and a decline in academic performance. Despite implementing various intervention strategies, including school-based programs, community involvement, and technology-driven solutions, their efficacy remains inconsistent due to challenges in enforcement and resource limitations. This review emphasizes the necessity for more robust, context-specific interventions and calls for further research to address the identified gaps, aiming to enhance the well-being and safety of students in Nigerian schools.